Optimization of workforce Allocation using linear programming - Banerjee, Sajal (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study explores the application of Linear Programming (LP) for optimizing workforce allocation in organizations. Efficient workforce management is essential for improving productivity, reducing operational costs, and meeting organizational objectives. Traditional workforce allocation methods often fail to address the complexities of modern operational environments, where multiple tasks, constraints, and resource limitations must be balanced. LP offers a mathematical framework to allocate workers optimally, considering factors like skill requirements, task deadlines, and budget restrictions. The objective of this research is to demonstrate how LP can be used to minimize labor costs while ensuring that workforce capacity aligns with the needs of various tasks. The paper formulates a model with decision variables representing worker assignments, an objective function minimizing labor costs, and constraints related to worker availability, task requirements, and budget limits. The model is solved using methods such as the Simplex algorithm and implemented with software tools like Excel Solver and MATLAB. The results reveal that LP provides an efficient solution to workforce allocation by maximizing productivity and adhering to constraints. This approach offers significant advantages over traditional methods, including cost savings and enhanced operational efficiency. Ultimately, the study shows that LP is a powerful tool for optimizing human resource utilization in diverse industries.